Development of Manyung Fruit Fish Process in Gang Dolly Surabaya - Nur Hapsari; Sani; Dedin F Rosida; Sri Djajati (Future Science)
Counseling and training of the Abdimas Program is an application of research results to make various fish products based on fish as an alternative high nutritious food products and a chance to be developed in Gang Dolly residents Surabaya to increase revenue.The method used in facilitating the improvement of fish processing skills in the area of Gang Dolly Surabaya is to conduct training with training methods are: lecture method, practice method and advisory methods for the sustainability of business activities and marketing results.The existing objective condition is that the low productivity of fishery producers produced during this time is more due to the weakness of human resources in the field of management, less professional organization, lack of mastery of processing technology and weak information and marketing, and the low quality of entrepreneurship from business actors. For this purpose, the training was conducted by the mothers of Putat Jaya (Gang Dolly) residents in making crackers from Manyung fish.In the field of economy or business, fish manyung is an economical fish that is important as a consumption fish that can be used as a money-producing material. Compared with the tengiri fish that are widely used as fish crackers, manyung fish is more promising to make money because the price of manyung fish is relatively cheaper than fish tengiri. And certainly the protein content in manyung fish is very high.